Genomics of gene banks: a case study in rice - McCouch, Susan R.; McNally, Kenneth L.; Wang, Wen; Hamilton, Ruaraidh Sackville (Wiley, 2012)
Only a small fraction of the naturally occurring genetic diversity available in the world's germplasm repositories has been explored to date, but this is expected to change with the advent of affordable, high‐throughput genotyping and sequencing technology. It is now possible to examine genome‐wide patterns of natural variation and link sequence polymorphisms with downstream phenotypic consequences. In this paper, we discuss how dramatic changes in the cost and efficiency of sequencing and genotyping are revolutionizing the way gene bank scientists approach the responsibilities of their job. Sequencing technology provides a set of tools that can be used to enhance the quality, efficiency, and cost‐effectiveness of gene bank operations, the depth of scientific knowledge of gene bank holdings, and the level of public interest in natural variation. As a result, gene banks have the chance to take on new life. Previously seen as “warehouses” where seeds were diligently maintained, but evolutionarily frozen in time, gene banks could transform into vibrant research centers that actively investigate the genetic potential of their holdings. In this paper, we will discuss how genotyping and sequencing can be integrated into the activities of a modern gene bank to revolutionize the way scientists document the genetic identity of their accessions; track seed lots, varieties, and alleles; identify duplicates; and rationalize active collections, and how the availability of genomics data are likely to motivate innovative collaborations with the larger research and breeding communities to engage in systematic and rigorous phenotyping and multilocation evaluation of the genetic resources in gene banks around the world. The objective is to understand and eventually predict how variation at the DNA level helps determine the phenotypic potential of an individual or population. Leadership and vision are needed to coordinate the characterization of collections and to integrate genotypic and phenotypic information in ways that will illuminate the value of these resources. Genotyping of collections represents a powerful starting point that will enable gene banks to become more effective as stewards of crop biodiversity.